The incidence and PCR detection of Campylobacter upsaliensis in dogs and cats - Steinhauserova, I; Fojtikova, K; Klimes, J (Letters in applied microbiology, 2000)
A study was made of the incidence of Campylobacter upsaliensis among dogs and cats suffering from acute or chronic diarrhoea; 225 dogs and cats were examined and 51 strains were identified, 16 (7%) of which were Camp. upsaliensis. When rectal swabs were taken from a control group of 126 dogs and cats without clinical symptoms, 19 Campylobacter spp. and four Camp. upsaliensis were identified. All the Camp. upsaliensis strains were isolated in dogs. The Campylobacter strains were identified on the basis of their biochemical characteristics and by PCR (polymerase chain reaction).
Keywords: průjem; psi; DNA bakterií; geny rRNA; kočky; Campylobacter; Dogs; Genes, rRNA; Diarrhea; RNA ribozomální 16S; zvířata; Cat Diseases; nemoci koček; RNA, Ribosomal, 16S; DNA, Bacterial; nemoci psů; incidence; Incidence; Campylobacter Infections; polymerázová řetězová reakce; Polymerase Chain Reaction; kampylobakterové infekce; Dog Diseases; Cats; Animals